Eco-Evolutionary Perspectives on Mixoplankton - Mansour, Joost Samir; Anestis, Konstantinos (Frontiers in Marine Science, 2021)
Mixotrophy, i.e., the capability of both phototrophy and phagotrophy within a single organism, is a prominent trophic mode in aquatic ecosystems. Mixotrophic strategies can be highly advantageous when feeding or photosynthesis alone does not sustain metabolic needs. In the current review, we discuss the functional types of mixotrophic marine protists (herein mixoplankton) within the context of evolution. Permanent plastids have been established in large due to gene transfer from prey and/or endosymbionts to the host cell. In some kleptoplastidic mixoplankton, prior gene transfers and active transcription of plastid related genes in the host can help maintain and extend retention of the current kleptoplast. In addition to kleptoplasts, the prey nucleus is also sometimes retained and actively transcribed to help maintain and even replicate the kleptoplasts. Endosymbiotic relations vary considerably in the extent to which hosts affect symbionts. For example, some endosymbionts are heavily modified to increase photosynthetic efficiency, or are controlled in their cell division. It can be proposed that many kleptoplasts and endosymbionts are in fact en route to becoming permanent plastids. Conditions such as increased temperature and limiting nutrients seem to favor phagotrophy in mixoplankton. However, responses of mixoplankton to changing environmental conditions like light irradiance, temperature, nutrient, and prey availability are variable and species-specific. Studying mixotrophs with temporary plastids could elucidate past and future evolutionary mechanisms and dynamics of processes such as phagotrophy and the establishment of (secondary) permanent plastids.